2010
DOI: 10.1002/hed.21270
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of interleukin‐1 by Epstein–Barr virus latent membrane protein 1 and its possible role in nasopharyngeal carcinoma cell growth

Abstract: EBV LMP1 is capable of upregulating IL-1alpha and IL-1beta secretions from epithelial cells and positively modulated by TNF-alpha. This may consequently contribute to tumor growth in patients with NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Our results showed that pro‐IL‐1β is induced by LMP1 in 4 NPC cell lines, NPC‐TW01, ‐TW02, ‐TW04 and HK1; similar induction was previously reported in NPC‐TW01 (Huang et al, 2010). Since inflammasome‐mediated release of IL‐1β can drive chronic inflammation with protumour activity (Fig 5C; Apte & Voronov, 2008), this might explain why in EBV‐associated cancers, the inflammasome genes are induced and activated by viral factors such as LMP1 and EBERs (Fig 7).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that pro‐IL‐1β is induced by LMP1 in 4 NPC cell lines, NPC‐TW01, ‐TW02, ‐TW04 and HK1; similar induction was previously reported in NPC‐TW01 (Huang et al, 2010). Since inflammasome‐mediated release of IL‐1β can drive chronic inflammation with protumour activity (Fig 5C; Apte & Voronov, 2008), this might explain why in EBV‐associated cancers, the inflammasome genes are induced and activated by viral factors such as LMP1 and EBERs (Fig 7).…”
Section: Discussionsupporting
confidence: 91%
“…IL‐1α is one of the major agonistic molecules of IL‐1 family, Oberyszyn et al [23] demonstrated that production of IL‐1α and other inflammatory cytokines induced leucocyte infiltration and resulted in carcinoma formation. The IL‐1α was significantly increased in NPC tissues and was detected in NPC tissues transplanted to nude mice [24, 25], and strong IL‐1α activity also was found in the medium from short‐term‐cultured fresh NPC biopsies [22]. In the NPC microenvironment, the IL‐1α might play an important role in tumor growth or progression [18, 25].…”
Section: Discussionmentioning
confidence: 99%
“…The IL‐1α was significantly increased in NPC tissues and was detected in NPC tissues transplanted to nude mice [24, 25], and strong IL‐1α activity also was found in the medium from short‐term‐cultured fresh NPC biopsies [22]. In the NPC microenvironment, the IL‐1α might play an important role in tumor growth or progression [18, 25]. Previous studies showed that genetic polymorphisms in the coding and promoter region sequences may regulate cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…NFκB signaling promotes growth and survival of the infected cells [36,92,93]. Through NFκB activation, LMP1 also induces IL-1α, IL-1β, and TNF-α in infected cells, favoring transformation as in the context of NPC development [94,95].…”
Section: Ebv Perturbation Of Prrsmentioning
confidence: 99%